Sovereign wealth : the role of state capital in the new financial order - A. Fry, Renée (Imperial College Press ; Distributed by World Scientific, 2011)
As the first major collection of papers on sovereign wealth funds and state-owned enterprises, this book provides an essential guide to the geo-political impact of these pools of capital on global markets. The rise of sovereign wealth funds and state-owned enterprises represents a fundamental shift in market dynamics. The potential fusion of political and commercial imperatives raises unresolved geo-political questions that have been sharpened by the vaporization of credit markets as a consequence of the global financial crisis. State-controlled pools of capital have now eclipsed hedge funds and private equity in terms of funds under management, and the question of their regulation is therefore now of utmost importance.This book highlights the interplay between legal, corporate and policy imperatives associated with the regulation of state capital. Including contributions from leading practitioners, policymakers and academics, it provides an essential guide to professionals and academics in the fields of finance and business. Là bộ sưu tập lớn đầu tiên về các quỹ tài sản có chủ quyền và các doanh nghiệp nhà nước, cuốn sách này cung cấp một hướng dẫn cần thiết về tác động địa chính trị của các nhóm vốn này trên thị trường toàn cầu. Sự gia tăng của các quỹ tài sản có chủ quyền và các doanh nghiệp nhà nước thể hiện sự thay đổi cơ bản trong động lực thị trường. Sự kết hợp tiềm năng giữa các mệnh lệnh chính trị và thương mại làm dấy lên những câu hỏi địa-chính trị chưa được giải đáp đã được làm rõ bởi sự bốc hơi của thị trường tín dụng do hậu quả của cuộc khủng hoảng tài chính toàn cầu. Các nguồn vốn do nhà nước kiểm soát hiện đã lấn át các quỹ đầu cơ và vốn cổ phần tư nhân về các quỹ được quản lý, và câu hỏi về quy định của họ do đó giờ đây trở nên vô cùng quan trọng. của vốn nhà nước. Bao gồm sự đóng góp của các nhà thực hành, nhà hoạch định chính sách và học giả hàng đầu, nó cung cấp một hướng dẫn cần thiết cho các chuyên gia và học giả trong lĩnh vực tài chính và kinh doanh.